تكرار العيوب الخلقية بين الولادات في مركز محافظة بابل لثلاث سنوات متعاقبة - هادي, رفاه (University of Thi-Qar Journal of Science, 2010)
The current study was conducted to search about the frequancy fetal defects and to  indicate the causes of fetal death among pregnancies. A retrospective study was conducted for three successive years. The study revealed that the fetal malformation was found in 0.33%, 0.323 % and 0.348 % for 2005, 2006 and 2007 respectively. The Anomalies of brain and spinal cord were the highest it reach a 38.8%, 33.3 % during 2006 and 20007 respectively. While the congenital anomalies of lower and upper limb during 2005 were 10.71% .The study also revealed that there were high percentage of undiagnosed anomalies. The present study showed that the percentages of fetal death were 3.35 %, 4, 16 % and 3.50 % for 2005, 2006 and 2007 respectively. These results revealed an importance of maternal care for pregnant women also other prospective study should be perform to high light this health problems.